Importance of mechanical action in a terminal disinfection process for decontamination of Clostridium difficile spores on hospital inert contact surfaces - Mafu, Akier Assanta; Massicotte, Richard; Pichette, Gilbert; Ahmad, Darakhshan (International Journal of Infection Control, 2015)
Although the relevance of surface disinfection is increasingly being accepted, there are still a number of issues which remain controversial. In hospital environments in Québec (Canada), a three-step technique of cleaning and disinfection is used following a case of Clostridium difficile contamination. This technique brings together three factors: chemical, mechanical and microbiological. The present study investigates the impact of the mechanical action during each of these three-steps on C. difficile spore populations. Thus, cleaning and sporicidal products were replaced by water. The reduction rate of C. difficile spores was evaluated on four contaminated types of surfaces commonly found in the hospital environment. They included: ceramic, polyvinyl chloride (PVC), melamine and 2-methylprop-2-enoate methyl (PMAM) bed lining According to the type of the inert surface, variation in the reduction rate of spores was observed. The bed lining was the most difficult surface to clean, followed by melamine. In contrast, the ceramic and PVC were the easiest surface to clean. For all the four surfaces, the average rate of spore loss associated with the various steps indicates that the mechanical action in the three-step process is important in reducing the risk associated with the presence of C. difficile spores on the hospital contact surfaces.